Event Influence Krui Pro International On The Income Of Msmes In Tanjung Setia Beach, West Coast District - Purnama Agung; Aida Neli; Tri Vitriyani Purwaningsih (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effect of the Krui Pro International event on the income of Micro, Small and Medium Enterprises (MSMEs) in Tanjung Setia Beach, West Pesisir Regency. This Event is an international surfing event that is held every year and is expected to increase tourist visits and have a positive impact on the local economy. The method used in this study is quantitative analysis with data collection through questionnaires distributed to 98 businesses around Tanjung Setia Beach. The results showed that there were significant differences in capital, turnover, and profit of MSMEs before and during the Krui Pro International event. Venture capital increased significantly, with 62.2% of respondents reporting an increase in capital during the event. In addition, business turnover also experienced a surge, where 61.2% of respondents felt a significant increase in turnover. This study concludes that the Krui Pro International event contributes significantly to local economic growth, especially for MSMEs, and recommends the need for continued support from the government and the development of more effective marketing strategies to maximize the benefits of the event.